A compact monomeric intermediate identified by NMR in the denaturation of dimeric triose phosphate isomerase. - Morgan, C; Wilkins, D; Smith, L; Kawata, Y; Dobson, C (2000)
The denaturation of triose phosphate isomerase (TIM) from Saccharomyces cerevisiae by guanidine hydrochlorids at pH 7.2 has been monitored by NMR spectroscopy in conjunction with optical spectroscopy. In the absence of denaturant, the hydrodynamic radius of 29.6(+/-0.25) A and the substantial chemical shift dispersion evident in the NMR spectrum are consistent with the highly structured dimeric native state of the protein. On the addition of 2. 2 M guanidine hydrochloride the effective hydrodynamic radius increases to 51.4(+/-0.43) A, consistent with that anticipated for the polypeptide chain in a highly unstructured random coil state. In 1.1 M guanidine hydrochloride, however, the effective hydrodynamic radius is 24.0(+/-0.25) A, a value substantially decreased relative to that of the native dimeric state but very close to that anticipated for a monomeric species with native-like compaction (23. 5 A). The lack of chemical shift dispersion indicates, however, that few tertiary interactions persist within this species. Far UV CD and intrinsic fluorescence measurements show that this compact intermediate retains significant secondary structure and that on average the fluorophores are partially excluded from solvent. Such a species could be important in the formation of dimeric TIM from its unfolded state.